Humanitarian aspects of overcoming the social crisis caused by Russian military aggression in Ukraine - Svydruk Irena, Kuczabski Aleksander, Sydorchuk Orystlava (Security and Defence Quarterly (Poland), 2025)
This paper analyses the humanitarian aspects of social security restoration in Ukraine. The integral social security level indicator was developed for this study. The state of social welfare in Ukraine in the pre-war period was investigated according to the author’s methodology. The losses of the social sphere in Ukraine as a result of Russia’s military aggression were also assessed according to the author’s approach. Further, Ukraine’s need for emergency humanitarian aid was discussed. Finally, the mechanisms for ensuring the humanitarian component of social security during the war were analysed. The article’s hypothesis starts with the consideration that even though the war is not over yet, some lessons can be identified, and those lessons should be considered in response to social security issues in the conditions of war and in the future post-war social reconstruction of Ukraine. Analysis of open information sources enables claims that the situation in the field of social security is catastrophic in the Ukrainian society. This is due to the war-related damages caused to the residential stock and social infrastructure facilities, the environmental consequences of the damages, and the risk of starvation. This article launches a global discussion on the role and place of humanitarian aspects in the provision of social security in a state affected by armed aggression. The study promotes the idea of overcoming the humanitarian crisis jointly by the united international community. Therefore, this paper is vital for a better understanding of the actual level of social security and its prognostication in post-war Ukraine.
Keywords: international cooperation; social security; war; humanitarian aid